Effects of the Order Parameter Anisotropy on the Vortex Lattice in UPt3 - Avers, K. E.; Gannon, W. J.; Leishman, A. W. D.; DeBeer-Schmitt, L.; Halperin, W. P.; Eskildsen, M. R. (Frontiers in Electronic Materials, 2022)
We have used small-angle neutron scattering to determine the vortex lattice phase diagram in the topological superconductor UPt3 for the applied magnetic field along the crystalline c-axis. A triangular vortex lattice is observed throughout the superconducting state, but with an orientation relative to the hexagonal basal plane that changes with field and temperature. At low temperature, in the chiral B phase, the vortex lattice undergoes a non-monotonic rotation with increasing magnetic field. The rotation amplitude decreases with increasing temperature and vanishes before reaching the A phase. Within the A phase an abrupt 15 degree vortex lattice rotation was previously reported by Huxley et al., Nature 406, 160-164 (2000)]. The complex phase diagram may be understood from competing effects of the superconducting order parameter, the symmetry breaking field, and the Fermi surface anisotropy. The low-temperature rotated phase, centered around 0.8 T, reported by Avers et al., Nature Physics 16, 531-535 (2020), can be attributed directly to the symmetry breaking field.